PENERAPAN EVIDANCE BASED NURSING TERAPI BERCERITA MENGGUNAKAN BONEKA TANGAN UNTUK MENGATASI MASALAH KETERLAMBATAN BICARA PADA ANAK USIA PRASEKOLAH - Clara Widya Mulya M (2022)
Speech delay is a problem that is often experienced by preschool children in their language development. It has been obtained data from the results of the assessment using the Denver II developmental measurement sheet that the patient manages and continues to experience disturbances in his language development as indicated by the discovery of more than one "D" sign item or delay in aspects of language development. One therapy that can overcome the problem of speech delay is speaking using hand puppets. The purpose of this study was to overcome speech delays in preschool children by providing interventions in the form of storytelling therapy using hand puppets. The case study was carried out by home visit and the intervention was given three times in a period of three weeks. Respondents involved in people's prayers. In the managed respondents, developmental measurements were carried out every week and were given therapeutic intervention and control respondents were measured for development every week. Before giving the intervention at each meeting, the authors measured language development using the Denver II development sheet. Then, after the intervention was given, the writer measured his language development again using the Denver II development sheet. At the end of the meeting, the authors found that the respondents managed to improve speaking skills, which were marked by passing marks or passing the three items measuring the development of Denver II.